The effect of inhibiting KPNB1-mediated nuclear import on cancer cell biology and inflammatory transcription factor signalling - Stelma, Tamara (Division of Medical Biochemistry and Structural Biology, 2018)
Cancer remains one of the major causes of morbidity and mortality globally. Many novel and innovative approaches have been employed to develop new chemotherapeutic strategies, of which targeted therapies aim to identify a molecular lesion or dysregulated pathway that cancer cells are dependent on. Research in our laboratory and others identified the nuclear import protein, Karyopherin β1 (KPNB1), to be overexpressed in various cancers and that inhibiting its expression blocks the proliferation of cancer cells. However, little is known about the potential role of KPNB1 in other cancer cell phenotypes and inflammatory signalling pathways. The aim of this study was to investigate the anticancer and anti-inflammatory effects of inhibiting nuclear import via KPNB1 and to characterise the in vivo effect of the small molecule inhibitor of nuclear import, INI-43, on tumour formation. Using siRNA and a small molecule inhibitor, INI-43, to inhibit KPNB1 we found that cervical cancer cell migration and invasion was significantly reduced. The reduced motility of cancer cells was associated with a decrease in MMP-2 and -9 expression and an increase in TIMP-1 and -2 expression following INI-43 treatment. This corresponded with a decrease in MMP-9 gelatinase activity in KPNB1-inhibited cervical cancer cells. Extended periods of KPNB1 inhibition lead to decreased proliferation and apoptosis. These changes in cancer cell biology when KPNB1 is inhibited may in part be due to its function as a nuclear transporter of transcription factors associated with cancer cell proliferation, migration and invasion. We therefore investigated the effects of KPNB1 inhibition on the nuclear localisation and transcriptional activity of key transcription factors; NFkB and AP-1, both having been implicated in many of the hallmarks of cancer. Immunofluorescent analysis and nuclear/cytoplasmic fractionation assays showed that KPNB1 inhibition blocked the nuclear localisation of NFkB. Electromobility shift assays confirmed a reduced NFkB binding to an NFkB DNA-binding sequence in the nuclear extract of KPNB1-inhibited cells. Luciferase reporter assays containing NFkB and/or AP-1 consensus binding sites showed reduced transcriptional activity for both transcription factors following KPNB1 inhibition. Associated with these changes in NFkB and AP-1 activity was reduced inflammatory cytokines; IL-6, IL-1β, TNF-α and GM-CSF target gene expression. To further characterise the role of INI-43 as a potential chemotherapeutic, the effects on tumour growth and development were investigated in an ectopic xenograft mouse model. INI-43 treatment significantly reduced tumour growth in mice and associated with the redistribution and reduction in KPNB1 levels. INI-43 treated tumours also showed altered morphological features including; better tissue differentiation and reduced inflammatory stromal infiltration, as well as reduced Ki-67 expression. The expression of extracellular matrix components and the cytoskeletal structure of cancer cells was analysed to further investigate the role of KPNB1 inhibition in tumour development. Inhibition of KPNB1 in cancer cells caused reduced expression of both collagen type IV and MMP-9. The redistribution of B-catenin and F-actin suggested that INI-43 treatment caused a loss of mesenchymal features required for tumour progression. The nuclear transport system has been of particular interest in recent years for the development of targeted anticancer drugs. However, most studies have focused on nuclear export inhibitors with little known on the potential of nuclear import inhibitors as anticancer drugs. This study provides evidence that inhibiting the nuclear import protein, KPNB1, has anti-inflammatory and anticancer effects and shows promise as an anticancer approach requiring further investigation.